2008
DOI: 10.1002/hep.22293
|View full text |Cite
|
Sign up to set email alerts
|

Effects of satavaptan, a selective vasopressin V2 receptor antagonist, on ascites and serum sodium in cirrhosis with hyponatremia

Abstract: for the HypoCAT study investigators* Hyponatremia in cirrhosis is associated with significant morbidity and mortality and complicates ascites management. Vasopressin receptor antagonists improve serum sodium concentration by increasing renal solute-free water excretion, but their effects on the management of ascites have not been assessed. Our aim was to investigate the effects of satavaptan, a highly selective vasopressin V 2 receptor antagonist, on ascites management and serum sodium in hyponatremic patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
169
1
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 185 publications
(175 citation statements)
references
References 21 publications
2
169
1
3
Order By: Relevance
“…1), 18 trials met the eligibility criteria or reported data for an eligible subgroup. Two trials assessed conivaptan, 13,14 four assessed lixivaptan, [15][16][17][18] three assessed satavaptan [19][20][21] and nine assessed tolvaptan. [22][23][24][25][26][27][28][29] There were no RCTs published assessing other known interventions such as urea, sodium tablets or mannitol.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…1), 18 trials met the eligibility criteria or reported data for an eligible subgroup. Two trials assessed conivaptan, 13,14 four assessed lixivaptan, [15][16][17][18] three assessed satavaptan [19][20][21] and nine assessed tolvaptan. [22][23][24][25][26][27][28][29] There were no RCTs published assessing other known interventions such as urea, sodium tablets or mannitol.…”
Section: Resultsmentioning
confidence: 99%
“…Otsuka (manufacturer of tolvaptan and funder of this review) provided information for six trials of tolvaptan vs placebo and the authors of two further trials responded. 14,20 A summary of the characteristics of the included trials is presented in Table 1. All 18 trials were randomized multicentre trials.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the agent has demonstrated utility in animal models and improved clinical outcomes in patients with SIADH or cirrhosis [65][66][67][68], its efficacy in CHF patients has yet to be determined.…”
Section: Chfmentioning
confidence: 99%